Insights into structural, spectroscopic, and hydrogen bonding interaction patterns of nicotinamide–oxalic acid (form I) salt by using experimental and theoretical approaches - Verma, Priya; Srivastava, Anubha; Tandon, Poonam; Shimpi, Manishkumar R. (Frontiers in Chemistry, 2023)
In the present work, nicotinamide-oxalic acid (NIC-OXA, form I) salt was crystallized by the slow evaporation of an aqueous solution. To understand the molecular structure and spectroscopic properties of NIC after co-crystallization with OXA; the experimental Infrared (IR), Raman spectroscopic signatures, X-ray powder diffraction (XRPD) and differential scanning calorimetry (DSC)) techniques were used to characterize and validate the salt. The density functional theory (DFT) methodology was adopted to perform all theoretical calculations by using B3LYP/6-311++G(d,p) functional/basis set. The experimental geometrical parameters were matched in good correlation with theoretical parameters of dimer than the monomer, due to the fact of covering the nearest hydrogen bonding interactions present in the crystal structure of the salt. The IR and Raman spectra of dimer showed the red (downward) shifting and broadening of bands among (N15-H16), (N38-H39), (C13=O14) bonds of NIC and (C26=O24), (C3=O1), (C26=O25) groups of OXA, hence involved in the formation of NIC-OXA salt. The atoms in molecules (AIM) analysis revealed that (N8-H9•••O24) is the strongest (conventional) intermolecular hydrogen bonding interaction in the dimer model of salt with the maximum value of interaction energy -12.1 kcal mol -1 . Further, the natural bond orbital (NBO) analysis of the Fock matrix showed that in the dimer model, the (N8-H9•••O24) bond is responsible for the stabilization of salt with an energy value of 13.44 kcal mol -1 . The frontier molecular orbitals (FMOs) analysis showed that NIC-OXA (form I) salt is more reactive and less stable than NIC, as the energy gap of NIC-OXA (form I) salt is less than that of NIC. The global and local reactivity descriptors parameters were calculated for the monomer and dimer models of salt. The electrophilic, nucleophilic and neutral reactive sites of NIC, OXA, monomer and dimer of salt were visualized by plotting the molecular electrostatic potential (MESP) surface. The study provides valuable insights into combining both experimental and theoretical results that could define the physicochemical properties of molecules.